Evolution of Dynamic Recrystallization in 5CrNiMoV Steel during Hot Forming - Zhiqiang Hu; Kaikun Wang (Advances in Materials Science and Engineering)
The dynamic recrystallization (DRX) behavior of 5CrNiMoV steel was investigated through hot compression at temperatures of 830–1230°C and strain rates of 0.001–10 s−1. From the experimental results, most true stress-strain curves showed the typical nature of DRX that a single peak was reached at low strains followed by a decrease of stress and a steady state finally at relatively high strains. The constitutive behavior of 5CrNiMoV steel was analyzed to deduce the operative deformation mechanisms, and the correlation between flow stress, temperature, and strain rate was expressed as a sine hyperbolic type constitutive equation. Based on the study of characteristic stresses and strains on the true stress-strain curves, a DRX kinetics model was constructed to characterize the influence of true strain, temperature, and strain rate on DRX evolution, which revealed that higher temperatures and lower strain rates had a favorable influence on improving the DRX volume fraction at the same true strain. Microstructure observations indicated that DRX was the main mechanism and austenite grains could be greatly refined by reducing the temperature of hot deformation or increasing the strain rate when complete recrystallization occurred. Furthermore, a DRX grain size model of 5CrNiMoV was obtained to predict the average DRX grain size during hot forming.